O PAPEL DA CÂMARA TÉCNICA DE PESCA DO COMITÊ DE BACIA HIDROGRÁFICA LAGOS SÃO JOÃO NA GESTÃO DA PESCA ARTESANAL NA LAGOA DE ARARUAMA - Silva, Carlos Augusto Barbosa da (2014)
This work presents a case study on the role of the Technical Chamber of Fishing (CTP) of the Intermunicipal Consortium Lagos São João (CILSJ) in mediating conflicts management of artisanal fisheries in the Araruama Lake (LA) region. The CTP is managed by the priorities of the National Water Resources Policy (PNRH), preservationist, as opposed to National Policy for the Sustainable Development of Fishing Activity (PNDSAP), for purposes of profiteering. The management of the Lagos São João River Basin by, CILSJ, prioritizes actions for the conservation and maintenance of water bodies for supplies, leaving in low priority the recovery of estuaries that launches the treated sewage and still untreated, precisely the places where it occurs fishing. The research subject was the representation of fishermen, who are the presidents of the colonies. Data collection occurred through interviews, direct observation, participant observation, documents, films, photographs, testimonials, also considering the actors in public management of local, state and federal fishing. The interviews were examined based on textual analysis. The research approach is qualitative. Artisanal fishing is practiced in the locality of small scale, using the fine craft, work occurs in communion and / or family. The co-management is a methodology for managing common resources most used nowadays in artisanal fisheries. The data revealed that the model of co-management of TCC is not adequate to mediate conflicts fishery in the locality. This study found that there is a union of the colonies through the CTP, but even so, the CTP mechanism does not allow greatest accomplishments are achieved by fishermen, given that the model of co-management is advisory only, where power public consultation, but makes the decision independently without sharing power management, thus no empowerment by fishermen. Thus, it is urgent to replace the co-management system exercised by the CTP, by a better one that allows greater participation of fishermen and not only their representations, management autonomy for fishermen, possibility of funding beyond preservation activities, but also to economic development of fisheries. Other models of co-management can substitute the CTP are the Extractive Reserve (RESEX), the Sustainable Development Reserve or Fishing Forum considering that these are the most successful models of co-management in the country and even in part of region, RESEX Arraial do Cabo. The confirmation of this study of the role played by the CTP regarding the co-management in LA is compatible with the shortcomings of the models the co-management of fisheries in Brazil, with less empowerment of fishermen against government and own submission and public fisheries management on public management environment. Although there is some academic research on fisheries, the literature on fisheries management in the city of LA is scarce, hampering the development of fisheries sustainability and the application of any management plan and indicates the urgency of the development of further investigation, in this work seeks to provide some contribution.